A regéci uradalom irányítása a 17. században - Veres, Tünde (Hallgatói Műhelytanulmányok, 2022)
Veres, Tünde: The management of the Regéc estate in the 17th century We can consider the 17th century as the period of development of the allodium and large estate system. This was the result of a long process that meant change in the life of an estate not only in economic sense, but it brought along the necessary change of the administrative system and its modernization too. While the economic role of the castles had been significant in the previous centuries, this indicates which role had mainly meant the leading of manorial yield. This system has come to an end gradually and a separation can be observed between the military and economic management by the 17th century. This decentralization and the gradual extension of the large estate system demanded a more divided, thus more professional economic apparatus. We can be faced with similar changes in the case of an estate in Regéc. The case of this demesne is interesting and the reason for this is that three eras can be distinguished during the time of the Rákóczi family’s possession – 1646–1685: date of the Rákóczi family’s possession; 1686–1691: the period of the Chamber of Szepes’s management, Kollonich’s and Klobusiczky’s guardianship, 1692–1711: Francis II Rákóczi is the owner –, and these three eras left an impression, and were based on each other. The most significant period is the second one, when Francis Klobusiczky kept an eye on the untroubled functioning of the Rákóczis’ whole estate-complex, but the provisor was the one who carried out the direct economic leading on the level of single estates. However, it would be an inaccurate and sim plified statement emphasizing only the role of provisor from this point of view, as the management of an estate was carried out within a government system built in a hierarchical way. In this complex system the duty of the employees, working on different levels, was the operation and maintenance of the former Rákóczi demesne. The aim of the study is to explore the government system and its working mechanism in the estate of Regéc based on the assignment and duty of the officials at the end of the 17th century. Since those persons who work in that employment have a significant position in the estate of Regéc, it is essential to study those kinds of conventions and accounts that are in connection with them. Therefore, the research of these mentioned documents constitutes the other focal point of this study.